Comparative electrochemical study on monolignols and dimers relevant for the comprehension of the lignification process. (September 2015) - Cottyn, Betty; Rivard, Michael; Majira, Amel; Beauhaire, Josiane; Allais, Florent; Martens, Thierry; Baumberger, Stéphanie; Ducrot, Paul-Henri
Graphical abstract: The objective of the present study is to complete previous electrochemical studies on coniferyl alcohol analogs by focusing on its dimers to further elucidate the lignification process, in order to distinguish between steric and electronic factors that inhibit oxidation. The results demonstrated that monolignols exhibit lower oxidation potential values than dimers and the β- O -4 dimer exhibited a quite peculiar behavior allowing two-electron oxidation. Moreover, we noticed that the pH turned out to affect the redox potential values. Phenol/phenol cation radical couples had a significantly higher potential than the corresponding phenate/phenoxy radical couple. These results emphasize the importance of understanding the specificities of in planta lignin growth and structure. Highlights: Dimers exhibit higher oxidation potentials than monolignols. β- O -4 dimer exhibits a peculiar behavior allowing two-electron oxidation. Phenol couples have a significantly higher potential than the corresponding phenate.